2017
DOI: 10.1108/ecam-01-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model for factors affecting construction and demolition waste management in Iran

Abstract: Purpose Factors influencing management of construction and demolition (C&D) waste within the Iranian context have yet to be investigated. The purpose of this paper is to define and address this knowledge gap, through development of a model to map the associations among the primary factors affecting C&D waste at project, industry and national levels. Design/methodology/approach A conceptual model is developed based on synthesising the findings of available studies on factors affecting C&D waste wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 72 publications
1
28
0
1
Order By: Relevance
“…In the recent decade, more studies in C&D waste diversion have been carried out in developing economies with an emphasis on the external and internal factors that may affect the C&D waste diversion practice. Governmental support was considered one of the main external factors, together with the local market and availability of urban space for landfilling (Nikmehr et al, 2017;Yuan, 2013). The key internal factors related to sustainable use of waste or waste efficiency include material procurement in the project delivery process (Ajayi et al, 2017a),…”
Section: Candd Waste Diversion Research In Developing Economiesmentioning
confidence: 99%
“…In the recent decade, more studies in C&D waste diversion have been carried out in developing economies with an emphasis on the external and internal factors that may affect the C&D waste diversion practice. Governmental support was considered one of the main external factors, together with the local market and availability of urban space for landfilling (Nikmehr et al, 2017;Yuan, 2013). The key internal factors related to sustainable use of waste or waste efficiency include material procurement in the project delivery process (Ajayi et al, 2017a),…”
Section: Candd Waste Diversion Research In Developing Economiesmentioning
confidence: 99%
“…Therefore, a coefficient was included (as a percentage) to estimate concrete waste and determine how this will affect total volume. Determining waste is a complex phenomenon that is almost entirely context-specific and based upon the on-site experiences and records of technicians [45,60]. This coefficient is included in the automated schedule designed for the present study.…”
Section: Logic and Analytical Considerationsmentioning
confidence: 99%
“…After importing the data to SmartPLS software the next steps are to draw the path model according to the hypothetical model, assigned name of constructs, connecting the independent variables with dependent variable and assigning the items to the respective construct and then the model is ready for modelling processes. Modelling process is commenced with PLS algorithm in the software with the number of iterations set at 300 [16]. Throughout the process, some of the items found unreliable having outer loadings below 0.5 which represents the correlations of the items with their respective latent variables.…”
Section: Model Developmentmentioning
confidence: 99%
“…To assess discriminant validity; two essential requirements should be met. These include the outer loading of each indicator should be higher than its loadings on other constructs, and according to Fornell-Larcker criteria, the square root of AVE of each construct should be higher than its highest correlation with any other construct [16,21]. Generated values of the model found that the outer loading of each item/manifest variable is higher in their relative independent variable than other independent variables.…”
Section: Assessing Measurement Modelmentioning
confidence: 99%